Management of Frontal Bone Fracture in the Pediatric Population: A Literature Review. Issue 3 (September 2022) - Ho, Kelly; Larson, Jordan H.; Reid, Russell R.; Naran, Sanjay
Background: The purpose of this study was to review the published literature in an effort to compare conservative and surgical interventions for pediatric frontal bone fractures and to create a treatment schematic that would result in the lowest morbidity. Methods: A literature review was performed to evaluate all publications related to frontal bone fracture treatments in the pediatric population. Patient age, fracture location, treatment modality, and complications were analyzed to elucidate whether conservative or surgical management is better for pediatric frontal bone fractures and to determine which type of management yields the lowest morbidity. Results: Sixteen articles met inclusion criteria. 88.89% of the included patients who underwent surgical repair did not experience any postoperative complications. The surgical treatments employed included craniotomy, implantation of custom macroporous hydroxyapatite prostheses, split calvarial graft, cranialization, and open reduction and internal fixation with either non-resorbable or resorbable plating systems. There were 17 cases of frontal bone fractures that were treated conservatively. Eleven of the 17 cases (61.1%) that were initially treated with conservative management resulted in complications; either a growing fracture or infection. Conclusions: No clear treatment algorithm for frontal bone fractures in each pediatric age group could be generated from the published literature. We likewise could not determine a clear distinction between the indications for conservative versus surgical management. However, we were able to conclude that primary surgical management for pediatric frontal bone fractures yields high success rates and few complications, regardless of the patient's age.